The need for surgery after endoscopic treatment of colorectal neoplasms is the most important outcome criterion - Rolny, Peter (Endoscopy, 2017)
Endoscopic submucosal dissection (ESD) is known to provide superior results in terms of en bloc and/or R0 resection compared with endoscopic mucosal resection. Therefore, ESD is also expected to provide superior clinical outcomes in terms of the need for supplementary surgery after endoscopic treatment. However, whether or not the clinical gain to the patient is sufficiently large to justify the cost and risk of ESD remains to be further evaluated.